Uterine cervix length by abdominal ultra sound in normal pregnant women 21 to 23 weeks - Huamán G., Moisés (2015)
Objectives: To determine the feasibility of cervical length measurement by transabdominal ultrasound at 20-23 weeks of gestation and to correlate this measurements with those obtained by tansvaginal ultrasound. Design: Observational cross-sectional study. Setting: Instituto Latinoamericano de Salud Reproductiva (ILSAR), Lima, Peru. Participants: Pregnant women. Methods: In 67 pregnant women with no risk factors for preterm delivery (PTD) measurement of the uterine cervix at 20-23 weeks of gestation was performed. Thirty women (30) underwent both transabdominal and transvaginal ultrasound measurement. Main outcome measures: Correlation of uterine cervix measurement by abdominal and transvaginal ultrasound. Results: The cervix could be measured satisfactorily by transabdominal measurement in 65 women (97%). There was a good correlation between transabdominal and transvaginal measurement  (r<.0.646, p<0.001) and there was no significant difference between both measurements (p:0.126).  Conclusions: The uterine cervix could be measured by transabdominal ultrasound in 97% of pregnant women. There was correlation between measurements obtained by transabdominal and transvaginal ultrasound.